The Relationship between Isometric Strength of the Lower Extremity Muscles and Incidence of Injuries in Lower Extremity in Young Football Players - parisa namazi; mostafa zarei; fariborz hovanloo (Sport Sciences and Health Research)
The risk of injury in football is high. Many researchers have introduced muscle strength as one of the most important internal risk factors, but few studies have examined the relationship between the isometric strength of muscles and incidence of injuries. Therefore, the aim of this study was to examine the relationship between isometric strength of lower extremity muscles and the incidence of injuries in football players and the power to predict these injuries. The sample of this study included 73 football players under 21 years of age. Before the beginning of the season, the anthropometric dimensions and isometric strength of lower extremity in dominant leg of each player were measured by Isokinetic device (Biodex system 4), then each player was followed up for 8 months and their injuries were recorded. The results of Cox regression test showed no significant relationship between isometric strength of the measured muscles and the incidence of injuries in lower extremity. According to these results, it is suggested that medical and technical staff of football teams use isometric tests to identify high risk players. Other strength evaluation methods such as isokinetic and isotonic strengths may be more effective.